Datos sobre la vegetación de andalucía. III. Series de vegetación caracterizadas por "Quercus suber" L. (Acta botánica malacitana, 1994)
Data about andalusian vegetation. III. Vegetation series with Quercus suber L. presence. Quercus suber woods are one of the natural forests with more diversity and more expanse in Andalusia (Spain). Quercus suber is a dominant or common species in eight vegetation series or subseries: Myrto communis-Querceto suberis S, Teucrio baetici-Querceto suberis S, Smilaci mauritanicae-Querceto rotundifoliae quercetoso suberis subsigmetum, Tamo communis-Oleeto sylvestris quercetoso suberis subsigmetum, San guisorbo hybridae-Querceto suberis S, Pyro bourgaeanae-Querceto rotundifoliae quercetoso suberis subsigmetum, Paeonio coriaceae-Querceto rotundifoliae quercetoso fagineae subsigmetum, var. of Quercus suber, Adenocarpo decorticantis-Querceto rotundifoliae quercetoso suberis subsigmetum. These vegetation series show peculiar sucesional dynamism of their communities depending on their traditional use, environmental factors and biogeographical location. Two new subasociations, Ulici eriocladi-Cistetum ladamferi cistetosum albidi and Phyllireo angustifoliae-Quercetum lusitanicae cytisetosurn tribracteojati, are described in this paper.